2019
DOI: 10.1111/gbi.12374
|View full text |Cite
|
Sign up to set email alerts
|

Exploring cycad foliage as an archive of the isotopic composition of atmospheric nitrogen

Abstract: Molecular nitrogen (N2) constitutes the majority of Earth's modern atmosphere, contributing ~0.79 bar of partial pressure (pN2). However, fluctuations in pN2 may have occurred on 107–109 year timescales in Earth's past, perhaps altering the isotopic composition of atmospheric nitrogen. Here, we explore an archive that may record the isotopic composition of atmospheric N2 in deep time: the foliage of cycads. Cycads are ancient gymnosperms that host symbiotic N2‐fixing cyanobacteria in modified root structures k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 91 publications
0
5
0
1
Order By: Relevance
“…Nitrogen supply depends on environmental conditions such as nutrient availability (Kipp et al, 2019). According to Shay et al (2015), nutrient de ciencies favour BNF, which may be why atmospheric N was the preferred N source in E. villosus growing in nutrient-de cient soils in Rhebu and Oceanview.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen supply depends on environmental conditions such as nutrient availability (Kipp et al, 2019). According to Shay et al (2015), nutrient de ciencies favour BNF, which may be why atmospheric N was the preferred N source in E. villosus growing in nutrient-de cient soils in Rhebu and Oceanview.…”
Section: Discussionmentioning
confidence: 99%
“…Vessey et al (2004) reported that although the N source preference of plants associated with N-xing bacteria has been extensively studied in plants such as legumes, the proportion of N derived from the atmosphere and soils in cycads is not studied. Also, studies such as those conducted by Kipp et al (2019) determine the composition of the 15 N isotope in cycad foliage to show that cycads partake in BNF, but the percentage N derived from the atmosphere is not quanti ed. In this study, we investigated the effects of soil characteristics (pH, nutrition, total cation, and exchange acidity) on cycad-microbe symbiosis and N preference of E. villosus growing in Rhebu and Oceanview.…”
Section: Introductionmentioning
confidence: 99%
“…Biological nitrogen fixation (BNF) is believed to be the main function of the coralloid root microbiome, in exchange for carbon sources from the host [9,10]. Indeed, in nitrogen-poor environments, cycad leaves carry the same nitrogen fractionation signal as their diazotrophic cyanobionts, confirming the plant's reliance on symbiotic BNF [11]. Other less studied functions for cycad cyanobionts and associated microbes might also be relevant for the symbiosis, such as diverse biological and ecological functions supported by natural products or specialized metabolites [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Also, many studies reported on the N-fixing bacteria associated with cycad species [20,24,25]; however, the influence of the bacterial isolates on plant nutrition and N source reliance is poorly understood. Moreover, studies that report on the composition of the 15 N isotope in cycad foliage, such as [26], do not report on the N reliance and the percentage of N derived from the atmosphere in cycads.…”
Section: Introductionmentioning
confidence: 99%